2019
DOI: 10.1039/c8nj04385j
|View full text |Cite
|
Sign up to set email alerts
|

A novel class of tyrosine derivatives as dual 5-LOX and COX-2/mPGES1 inhibitors with PGE2 mediated anticancer properties

Abstract: Leukotriene and prostaglandin pathways are controlled by the enzymes, LOX and COX/mPGES1 respectively and are responsible for inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…LOXs catalyze the transformation of arachidonic acid into three types of hydroxyeicosatetraenoic acids (HETEs)-5-HPETE or 5-HETE by 5-LOX, 12-HETEs by 12-LOX and 15-HETEs by 15-LOX. 5-HETE is the precursor of leukotriene LTA 4 , which is converted into lipid mediators LTB 4, LTC 4, LTD 4, LTE 4 that induce asthma and inflammation [196,197]. Studies have found that 5-HETE and 5-HPETE stimulate the generation of superoxide in human neutrophils, and trigger the ROS stress [198].…”
Section: Arachidonic Acid Metabolism Pathway and Inflammationmentioning
confidence: 99%
“…LOXs catalyze the transformation of arachidonic acid into three types of hydroxyeicosatetraenoic acids (HETEs)-5-HPETE or 5-HETE by 5-LOX, 12-HETEs by 12-LOX and 15-HETEs by 15-LOX. 5-HETE is the precursor of leukotriene LTA 4 , which is converted into lipid mediators LTB 4, LTC 4, LTD 4, LTE 4 that induce asthma and inflammation [196,197]. Studies have found that 5-HETE and 5-HPETE stimulate the generation of superoxide in human neutrophils, and trigger the ROS stress [198].…”
Section: Arachidonic Acid Metabolism Pathway and Inflammationmentioning
confidence: 99%
“…When IL-1 β binds to its receptor, the activity of COX-2 is increased. COX-2 has a catalytic role in the conversion of arachidonic acid to PGE and PGE2 under the action of PGE synthetase [ 22 ]. PGE2 can increase vascular permeability and dilate blood vessels, resulting in bronchial mucosal edema, increased gland secretion, and airway obstruction by exudates [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Puratchikody et al 187 synthesized a series of novel tyrosine derivatives to favor the inhibition of 5-LOX and PGE 2 production. Most of the synthesized derivatives could be further optimized and developed as drugs against inflammation and cancer.…”
Section: Recently Reported Cox Inhibitorsmentioning
confidence: 99%